1996
DOI: 10.1046/j.1365-2559.1996.d01-418.x
|View full text |Cite
|
Sign up to set email alerts
|

Granulomas and Hepatitis C

Abstract: Hepatitis C (HCV) is associated with a number of characteristic histological features. A recent paper has identified an increased frequency of granulomas in resection specimens from cases of HCV. We have carried out a retrospective study of 155 cases of HCV to assess the frequency of granulomas in biopsy specimens. We had two control groups: 151 cases of hepatitis B (HBV) and 129 cases of alcohol induced liver disease. Granulomas were found in 14 cases of HCV (10%), three cases of HBV (2%) and three cases of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
2
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 4 publications
0
9
2
1
Order By: Relevance
“…Chronic HCV has only been recognised as a cause of hepatic granulomas since the availability of routine serological testing in 1991, and was therefore not described as a cause of hepatic granulomas in the previous large UK series. 4 7 8 10 Hepatic granulomas have been described in up to 10% of liver biopsies from HCV infected patients, [12][13][14][15] although the clinical relevance of this finding is unknown. 16 17 Thus, we expected that there would have been a smaller proportion of ''idiopathic'' cases in our series.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic HCV has only been recognised as a cause of hepatic granulomas since the availability of routine serological testing in 1991, and was therefore not described as a cause of hepatic granulomas in the previous large UK series. 4 7 8 10 Hepatic granulomas have been described in up to 10% of liver biopsies from HCV infected patients, [12][13][14][15] although the clinical relevance of this finding is unknown. 16 17 Thus, we expected that there would have been a smaller proportion of ''idiopathic'' cases in our series.…”
Section: Discussionmentioning
confidence: 99%
“…12,38,67e70 Hepatitis B The data for hepatic granuloma formation in hepatitis B infection is limited. However, a study by Goldin and colleagues 67 reported hepatic granulomas in 2% (3/151) of patients with chronic hepatitis B infection. As with hepatitis C, it is imperative that other granulomatous diseases such as tuberculosis, brucellosis, sarcoidosis and drug reactions be excluded.…”
Section: Hepatitis Cmentioning
confidence: 98%
“…Emile et al [9] found that the explants of 5 of 52 patients undergoing liver transplantation for cirrhosis from HCV had epithelioid granulomas, and none of these patients had evidence of any other diseases such as tuberculosis or sarcoidosis. Goldin et al [4] found in a retrospective study that there were granulomas in the liver biopsy specimens of 14/155 patients with HCV compared with only 3/151 with HBV and 3/129 with alcoholic liver disease. Yamamoto et al [6] found unexplained granulomas in 2/273 (0.73%) liver biopsies of patients with chronic HCV.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases the granulomas are associated with a clinical picture which includes a high alkaline phosphatase and hepatomegaly; but these features are frequently absent. A significant percentage of liver biopsies performed today are for the staging of chronic hepatitis C. Granulomas have been reported with possible increased frequency in patients with hepatitis C with both mild disease as well as in explants [4][5][6][7][8] . It has been postulated that hepatitis C virus (HCV) may have a role in granuloma formation [9] .…”
Section: Introductionmentioning
confidence: 99%